URGENSI HEUTAGOGY DALAM PELAKSANAAN PEMBELAJARAN PENULISAN NASKAH DRAMA DI UNIVERSITAS PERADABAN (THE URGENCY OF HEUTAGOGY IN THE LEARNING OF DRAMA SCRIPT WRITING AT PERADABAN UNIVERSITY) - Cintya Nurika Irma; Noviea Varahdilah Sandi; Bagiya Bagiya (Balai Bahasa Jawa Barat, 2021)
This study aims to describe and explain the urgency of Heutagogy in learning to write drama scripts at the University Peradaban. This research is a case study with a sample of second semester students of PBI (Indonesian Language Education) FKIP (Faculty of Teacher Training and Education), University Peradaban. This study uses technical and source triangulation to triangulate data. The results showed that heutagogy in drama script writing using local wisdom was able to improve (a) critical thinking, (b) independence, (c) communication, and (d) lifelong learning. In addition, the successful application of drama script writing based on local wisdom is carried out through a process of desire, ability, means, and need.